Awareness and Acceptance of Cultural Diversity in Healthcare Settings - Sharma, Akriti; Dhakal, Binita; Basnet, Ijana; Tiwari, Mamata; Gurung, Menu; Adhikari, Narayani; Shrestha, Rina (International Journal of Atharva, 2025)
Background: Nepal's multi-ethnic and multilingual society is characterized by a deep-rooted caste-based hierarchy, which has historically led to the marginalization of groups like Dalits, Janajatis, and Madhesis. This social stratification creates significant barriers to equitable healthcare access and utilization. Cultural competence among healthcare providers is therefore essential for ethical practice and quality care, yet factors limiting access for ethnic minorities remain poorly understood. Objectives: This study aimed to (1) assess the awareness and acceptance of cultural and religious diversity in healthcare among individuals in Nepal, and (2) examine gender-based differences in this awareness and acceptance. Methods: A quantitative cross-sectional study was conducted with a sample of 247 participants, including the general public, healthcare providers, patients, and students. Data were collected via an online questionnaire using simple random sampling. The instrument included a demographic section, a diversity awareness scale, and a diversity acceptance and inclusivity scale based on a Likert scale. Data were analyzed using descriptive statistics and independent samples t-tests to compare gender differences. Findings: Participants demonstrated a strong consensus (Mean=3.77) that healthcare institutions must cater to diverse patient needs. Awareness of how cultural/religious backgrounds affect healthcare preferences was moderate (Mean=3.17). A significant gender difference was found in awareness, with females (M=2.89) scoring significantly higher than males (M=2.73, p=0.030). However, no significant gender difference was observed in the level of acceptance of diversity (p=0.280). Conclusion: While there is a strong overall acceptance of the need for diversity in healthcare, awareness of its specific impact is only moderate and varies by gender. Females show a significantly greater understanding of diversity issues compared to males. Implication: The findings highlight a critical need for targeted educational interventions and cultural competence training for both healthcare professionals and the public, with a specific focus on improving awareness among male demographics. This is vital for developing more inclusive and equitable healthcare services in Nepal's diverse society.